1987
DOI: 10.1002/polb.1987.090250509
|View full text |Cite
|
Sign up to set email alerts
|

Polyethylene–isotactic polypropylene epitaxy: Analysis of the diffraction patterns of oriented biphasic blends

Abstract: Diffraction patterns of oriented blends of isotactic polypropylene (iPP) and polyethylene (PE) published recently by several authors are analyzed on the basis of a unique epitaxial relationship between the iPP and PE crystal lattices. The contact planes are (100)PE and (010)iPP, and the PE chains lie at 50° to the iPP chain axis, parallel to the helical path of the iPP helices, which is formed by rows of side‐group methyls.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
0

Year Published

1994
1994
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(52 citation statements)
references
References 9 publications
1
51
0
Order By: Relevance
“…This special reflection can be ascribed to the epitaxial growth of PE lamellae onto PP lamellae, as it has been reported in many researches . PE crystallizes on the surface of the iPP substrate, with its chain ±50° apart from the chain direction of the iPP substrate, and two contact planes are assigned to be (100) PE and (010) PP …”
Section: Resultssupporting
confidence: 56%
See 2 more Smart Citations
“…This special reflection can be ascribed to the epitaxial growth of PE lamellae onto PP lamellae, as it has been reported in many researches . PE crystallizes on the surface of the iPP substrate, with its chain ±50° apart from the chain direction of the iPP substrate, and two contact planes are assigned to be (100) PE and (010) PP …”
Section: Resultssupporting
confidence: 56%
“…Although these methods have successfully obtained the epitaxial structures in practical samples, making it possible for the industrial production of iPP/PE blends with special epitaxial structures. One thing to note is that the specific morphology of epitaxial structures in those samples is not clear, even though X‐ray patterns do give a strong proof of the existence of epitaxial structures according to many previous researches . Obviously, there is reason to believe that the morphology is probably a little changed.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…5(b,c)]. The herringbone texture, characteristic of epitaxially crystallized polyethylene, 16,17 was evident in several places.…”
Section: Films With Znpementioning
confidence: 96%
“…Epitaxial crystallization of polyethylene on polypropylene is well documented. 16,17 A near lattice match of the unit cells results in the growth of polyethylene lamellae at a characteristic 42°angle to the polypropylene lamellar long axis. The absence of oriented lamellar growth of znPE at the interface with hmsPP indicated that the amorphous interfacial layer prevented intimate contact of the crystallizable hmsPP and znPE constituents.…”
Section: Bulk Morphologymentioning
confidence: 99%